ChAdOx1 nCoV-19 Vaccine and Thrombosis with Thrombocytopenia Syndrome among Adults: A Systematic Review - Homa Faghihi; Negar Mottaghi-Dastjerdi; Mohammad Sharifzadeh; Nader Rahimi Kakavandi (Tabriz University of Medical Sciences, 2023)
Several vaccine-induced thrombotic thrombocytopenia syndrome (VITTS) cases have been reported after the ChAdOx1 nCov-19 vaccination. The current study systematically reviewed the reported post-ChAdOx1 nCoV-19 vaccination thrombotic thrombocytopenia cases. Their laboratory and clinical features, as well as the diagnostic and therapeutic measures, were investigated. Online databases were searched until 25 August 2021. Studies reporting post-ChAdOx1 nCov-19 vaccination thrombotic thrombocytopenia syndrome (TTS) were included. Overall, 167 cases (21-77 years old) from 53 publications were included showing a female dominance of 1.75 times. About 85% of the cases exhibited the primary symptoms within the first two weeks post-vaccination. Headache was the most common initial symptom (>44.2%), and hemorrhage/thrombotic problems (22.46%), as well as discoordination/weakness/numbness/ hemiparesis/cyanotic toes (19.6%), were the most prevalent uncommon initial symptoms. Prothrombin time (PT), D-dimers, and C-reactive protein were the most remarkable increased laboratory parameters in 50.6%, 99.1%, and 55.6% of cases, respectively. In comparison, platelet and fibrinogen were the most remarkable decreased laboratory parameters in 92.7% and 50.5% of cases, respectively. Most VITT cases presented with cerebral venous thrombosis/cerebral venous sinus thrombosis, supraventricular tachycardia, transverse sinus/cerebral thrombosis, pulmonary embolism, and cerebral hemorrhage. Anti-PF4 antibody measurement through immunoassays and functional assays were positive in 86.2% and 73% of cases, respectively. About 31% of the cases died. Early diagnosis and proper therapeutic measures are important in ChAdOx1 nCov-19 vaccine-induced VITTS patients. Therefore, experts are recommended to know the corresponding clinical and laboratory features, as well as diagnostic methods. Elucidation of the pathophysiologic mechanism of ChAdOx1 nCov-19 vaccine-induced TTS deserves further investigation.